A large family of anti‐activators accompanying XylS/AraC family regulatory proteins - Santiago, Araceli E. (Mol Microbiol, 2016)
AraC Negative Regulators (ANR) suppress virulence genes by directly down‐regulating AraC/XylS members in Gram‐negative bacteria. In this study, we sought to investigate the distribution and molecular mechanisms of regulatory function for ANRs among different bacterial pathogens. We identified more than 200 ANRs distributed in diverse clinically important gram negative pathogens, including Vibrio spp., Salmonella spp., Shigella spp., Yersinia spp., Citrobacter spp., enterotoxigenic (ETEC) and enteroaggregative E. coli (EAEC), and members of the Pasteurellaceae. By employing a bacterial two hybrid system, pull down assays and surface plasmon resonance (SPR) analysis, we demonstrate that Aar (AggR‐activated regulator), a prototype member of the ANR family in EAEC, binds with high affinity to the central linker domain of AraC‐like member AggR. ANR‐AggR binding disrupted AggR dimerization and prevented AggR‐DNA binding. ANR homologs of Vibrio cholerae, Citrobacter rodentium, Salmonella enterica and ETEC were capable of complementing Aar activity by repressing aggR expression in EAEC strain 042. ANR homologs of ETEC and Vibrio cholerae bound to AggR as well as to other members of the AraC family, including Rns and ToxT. The predicted proteins of all ANR members exhibit three highly conserved predicted α‐helices. Site‐directed mutagenesis studies suggest that at least predicted α‐helices 2 and 3 are required for Aar activity. In sum, our data strongly suggest that members of the novel ANR family act by directly binding to their cognate AraC partners.